Arthrofibrosis risk factors after anterior cruciate ligament reconstruction - Dauty, Marc; Menu, Pierre; Grondin, Jérôme; Crenn, Vincent; Daley, Pauline; Fouasson-Chailloux, Alban (Frontiers in Sports and Active Living, 2023)
Introduction Knee arthrofibrosis is a disabling complication after anterior cruciate ligament reconstruction (ACLr). Different risk factors have been studied but are still controversial because of a diagnosis made only during reoperations for the treatment of the stiffness, which underestimates the occurrence rate. We aimed to confirm risk factors of arthrofibrosis after ACLr in case of clinically made diagnoses. Methods Ninety-two athletes with clinically diagnosed arthrofibrosis, complicating a primary ACLr, were compared to 482 athletes with ACLr without any complications. Usually considered risk factors were studied: age under 18, female, Body Mass Index (BMI ≥ 25), high sport level, time from ACL injury to ACLr < 1 month, Bone-Patella-Tendon-Bone surgical procedure (BPTB), meniscal repair, and intensive rehabilitation. Binary logistic regression was carried out to confirm or refute these risk factors. Results Female, time from ACL injury to ACLr < 1 month, BPTB procedure, meniscal repair, and BMI ≥ 25 were not confirmed as risk factors. Previous competitive sport level assessed by Tegner score was the only risk factor identified, OR: 3.56 (95%IC: 2.20–5.75; p = 0.0001). Age < 18, OR: 0.40 (95%IC: 0.19–0.84; p = 0.015) and inpatient rehabilitation program, OR: 0.28 (95%IC: 0.17–0.47; p = 0.0001), were protective factors. Discussion Competitive athletes are at risk of arthrofibrosis after ACLr and should benefit from protective inpatient rehabilitation program.